The Problems Encountered by English Foreign Language Learners in English Speaking Skill: Systematic Literature Review - Fitriyanti, Indah Dwi; Malihah, Noor (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
ABSTRACT The objective of this research is to investigate what problems are encountered by EFL learners. English speaking skill is one of the most important skills in English. Then Speaking skill is not easy to learn. Several literature reviews show the learners’ problems with English speaking skills. This Systematic Literature Review analyzes 20 articles related to the problems encountered by EFL learners in English speaking skills. The result of this research showed that the learners' problems in English speaking skills covered linguistic problems and non-linguistic problems. Problems encountered by learners showed that linguistic problems involve a lack of vocabulary, pronunciation, fluency, and grammar. Then non-linguistic problems encountered by learners, showed that there are so many non-linguistic problems, but the most common and often found non-linguistic problems are felt not confidence, fear of mistakes, shyness, nervousness, anxiety, lack of motivation, afraid negative response, mother tongue, insecurity, uneven participant, never practice, nothing to say.